THE DEVELOPMENT OF WORKSHEET IN THE EXPERIMENT OF CREATING INDICATOR PAPERS - Sari Sari; Yuniartika Yuniartika; Siti Sopiah (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2020)
This study aimed to describe the worksheet's appearance and analyze the worksheet's validation test result based on POE (Predict, Observe, Explain). This research's objectives were to describe the development of a worksheet used in creating indicator papers from Aerva sanguinolenta plants and analyze the feasibility test result on its format. The stages of developing worksheets consist of preparation (define) the stage by analyzing research literature on indicator papers from Aerva sanguinolenta, planning stage by designing laboratory activities in worksheets, and development stage by conducting trials on worksheet products. The worksheet's feasibility was then tested. The results were validated with the average r-count value from the validators of 0.92, the average feasibility value percentage of 92%, the average r-count value from the students of 0.93, and the average feasibility value percentage of 93%. Therefore, the worksheet can be used as a learning aid for students in conducting experiments.